Review of care and management of pregnant women during COVID-19 pandemic - Manu Goyal; Pratibha Singh; Nitesh Melana (Elsevier, 2020)
Coronavirus disease-19 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Covid-19 pandemic began in the end of 2019 and spread all over the world in a short duration of time. Measures have been taken such as social distancing, compulsory lockdown and restriction of activities so as to prevent spread of virus. It has posed problem to both the antenatal women and maternity care workers. The care and management of pregnant women is an essential service to identify high-risk mothers and also to have good pregnancy outcome for both mother and baby. Any delay in this may lead to catastrophe, hence this issue needs to be addressed properly. This review briefs about the literature available on antenatal care during covid-19 pandemic. Pregnancy is not very adversely affected by the virus itself but extra caution should be taken to prevent and complications should they arise. The norms of social distancing by patients and wearing personal protective equipment by hospital staff, testing of pregnant women should be followed as per regional and national guidelines. This will help ensure safety of all people along with care to the expecting mother. The presence of covid-19 infection should not deter women from receiving antenatal care nor should the obstetric treatment be delayed during labor. Decision for timing and mode of delivery should be individualised based on obstetric indications and maternal-fetal status.